2006
DOI: 10.1097/01.mlg.0000197930.93582.32
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose‐Positron Emission Tomography/Computed Tomography Imaging in Patients with Carcinoma of the Larynx: Diagnostic Accuracy and Impact on Clinical Management

Abstract: The performance of PET/CT is better than standalone PET or CT in patients with cancer of the larynx. PET/CT had a major impact on management of 59% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 18 publications
1
43
1
2
Order By: Relevance
“…We obtained from their combination a final 95% CI 0.51-0.88 for Se and a value of 95% CI 0.55-0.96 for Sp, reporting a very high I 2 value for both Se (87.7%) and Sp (95.91%), where the lowest rates of Se were reported by Hartl et al (220) and Allegra and colleagues (218), whilst Gordin and Beser (191,222) showed the lowest rate for Sp. Here the hypothesis of hegemony among these different studies was not statistically significant ( Figure 16).…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…We obtained from their combination a final 95% CI 0.51-0.88 for Se and a value of 95% CI 0.55-0.96 for Sp, reporting a very high I 2 value for both Se (87.7%) and Sp (95.91%), where the lowest rates of Se were reported by Hartl et al (220) and Allegra and colleagues (218), whilst Gordin and Beser (191,222) showed the lowest rate for Sp. Here the hypothesis of hegemony among these different studies was not statistically significant ( Figure 16).…”
mentioning
confidence: 85%
“…Two recent studies opened new directions for applying MRI for laryngeal imaging: MR microimaging of excised larynges confirmed valid high-resolution imaging of laryngeal tissue microstructure (189), and dynamic MRI of laryngeal and vocal fold vibrations was realized for the first time for measuring of laryngeal structures and glottal parameters in dynamic function (190). (191). PET is a functional imaging modality assessing the metabolic status of tumors and has proved superior to CT and MRI in differentiating recurrence from post-radiation effects or scar in patients with carcinoma of the larynx (191,192).…”
Section: ! -Mrimentioning
confidence: 99%
See 3 more Smart Citations